Neuronal Responses to Physiological Stress - Kagias, Konstantinos; Nehammer, Camilla; Pocock, Roger (Frontiers in Genetics, 2012)
Physiological stress can be defined as any external or internal condition that challenges the homeostasis of a cell or an organism. Physiological stress can be divided into three different aspects: environmental stress, intrinsic developmental stress and aging. Throughout life all living organisms are challenged by changes in the environment. Fluctuations in oxygen levels, temperature and redox state for example, trigger molecular events that enable an organism to adapt, survive and reproduce. In addition to external stressors, organisms experience stress associated with morphogenesis and changes in inner chemistry during normal development. For example, conditions such as intrinsic hypoxia and oxidative stress, which result from an increase in tissue mass, have to be confronted by developing embryos in order to complete their development. Finally, organisms face the challenge of stochastic accumulation of molecular damage during aging that results in decline and eventual death. Studies have shown that the nervous system plays a pivotal role in responding to stress. Neurons not only receive and process information from the environment but also actively respond to various stresses to promote survival. These responses include changes in the expression of molecules such as transcription factors and microRNAs that regulate stress resistance and adaptation. Moreover, both intrinsic and extrinsic stresses have a tremendous impact on neuronal development and maintenance with implications in many diseases. Here, we review the responses of neurons to various physiological stressors at the molecular and cellular level.